Answer: 4=-2x -1 and y=-1 2x
Answer:
![\frac{(6p+14)}{p}](https://tex.z-dn.net/?f=%5Cfrac%7B%286p%2B14%29%7D%7Bp%7D)
Step-by-step explanation:
![(p+\frac{7}{3})(\frac{6}{p})](https://tex.z-dn.net/?f=%28p%2B%5Cfrac%7B7%7D%7B3%7D%29%28%5Cfrac%7B6%7D%7Bp%7D%29)
Making denominator same in first bracket we get
![(\frac{3p+7}{3})(\frac{6}{p})](https://tex.z-dn.net/?f=%28%5Cfrac%7B3p%2B7%7D%7B3%7D%29%28%5Cfrac%7B6%7D%7Bp%7D%29)
![(\frac{(3p+7)*6}{3*p})](https://tex.z-dn.net/?f=%28%5Cfrac%7B%283p%2B7%29%2A6%7D%7B3%2Ap%7D%29)
Dividing 6 by 3 we get 2
![(\frac{(3p+7)*2}{p})](https://tex.z-dn.net/?f=%28%5Cfrac%7B%283p%2B7%29%2A2%7D%7Bp%7D%29)
using distributive law
![(\frac{6p+14}{p})\\](https://tex.z-dn.net/?f=%28%5Cfrac%7B6p%2B14%7D%7Bp%7D%29%5C%5C)
Hence this is our answer
A) (-4,2π/3)
b) (4,4π/3)
c) (-2,π/3)
d) (2,5π/3)
The answer is D.
Hope I helped
Answer:
see explanation
Step-by-step explanation:
let ∠BCE = x then ∠ECD = 5x - 6 and
∠BCE + ∠ECD = ∠BCD, substitute values
x + 5x - 6 = 162, that is
6x - 6 = 162 ( add 6 to both sides )
6x = 168 ( divide both sides by 6 )
x = 28
Hence
∠BCE = x = 28°
∠ECD = 5x - 6 = (5 × 28) - 6 = 140 - 6 = 134°